ANALISIS KONTRIBUSI DAN EFEKTIFITAS PEMUNGUTAN PAJAK REKLAME UNTUK MENINGKATKAN PENDAPATAN ASLI DAERAH KOTA SURABAYA - FIRMANSYAH, ALFIAN (Jurnal Akuntansi AKUNESA, 2015)
Surabaya is one of the biggest city in Indonesia, after Jakarta. So there are many investors that uses Surabaya crowd to build an advertisement. This research is used to analyze the contribution and the effectiveness of advertisement tax in Surabaya during 2009-2013. This research uses qualitative method within case study. This research conclude that there are 2 major factors that impact degression of advertisement tax, which is the less effectiveness to collect advertisement tax debt, and another local tax that significally increased.Keywords: effectiveness, contribution, advertisement tax, Surabaya